Imaging Workup of Trauma Patients - Mal, Rahul; Chan, Kelvin L.S.; Gupta, Amit (Digestive Disease Interventions, 2025)
Trauma remains a leading cause of morbidity and mortality worldwide. Rapid and accurate evaluation of trauma patients is crucial to guiding optimal management. Imaging has become a cornerstone in trauma assessment, playing a critical role in identifying life-threatening injuries and providing detailed information about the extent of trauma to various body systems. This article reviews current imaging applications in trauma and addresses advancements in the utilization of imaging in the trauma workflow.
Keywords: trauma; imaging; interventional radiology